CRIMINAL LIABILITY AND THE APPLICATION OF MENS REA IN THE CRIMINAL OFFENSE OF INTERCEPTION IN INDONESIA - Prasetyo, Ekky Aji; Lasmadi, Sahuri; Erwin (Hukum Responsif, 2024)
The aim of this thesis research is to find out and analyze the findings of criminal liability related to mens rea in the crime of interception, and to find out and analyze the formulation of future norms regarding the regulation of criminal liability related to mens rea in the crime of interception. The problem formulation is how is the regulation of criminal liability related to mens rea in the crime of interception? and what will be the formulation of future norms regarding the regulation of criminal liability relating to mens rea in the crime of interception? The research method used in this research is normative juridical which reveals that normative legal research or doctrinal legal research is research on law that is conceptualized and developed on the basis of the doctrine adhered to by the conceptualizer or its development. In this research, the approaches that will be used are the conceptual approach, the statutory approach, and the comparative approach. Analysis of legal materials is carried out after all legal materials have been collected and then analyzed in a normative juridical manner. The analysis is carried out by evaluating legal norms based on the constitution on developing problems as a process to find answers to the main problems. Analysis of legal materials is carried out using inventory techniques, systematization techniques and interpretation techniques. The results of this research are that it is necessary to differentiate the mens rea for perpetrator witnesses who carry out interception or wiretapping so that their actions cannot be categorized as criminal liability, and there is a need for special protection for people who carry out interception or wiretapping in the public interest for certain criminal acts, such as criminal acts. corruption crimes, human trafficking crimes, money laundering crimes, and other special crimes.